Annual Report 2009-10 - Planning Commission (Planning Commission, 2009)
Constituted in March, 1950 by a Resolution of the Government of India, the Planning Commission works under the overall guidance of the National Development Council. The Planning Commission in consultation with the Central Ministries and the State Governments formulates Five Year Plans and Annual Plans and oversees their implementation. The Commission also functions as an advisory planning body at the apex level
Government of India Planning Commission
Government of India Planning Commission